2002
DOI: 10.1023/a:1014904701723
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Activity and Acetylcholinesterase Glycosylation are Altered in Human Breast Cancer

Abstract: Increasing evidence supports the involvement of cholinesterases in tumorigenesis. Several tumour cells show ChE activity, while the acetyl- (AChE) and butyrylcholinesterase (BuChE) genes are amplified in leukemias, ovarian carcinoma and other cancers. ChE activity was measured in 31 samples of tumoral breast (TB) and 20 of normal breast (NB). Despite the wide variations observed, BuChE predominated over AChE both in TB and NB. The mean AChE activity in NB was 1.61 nmol of the substrate hydrolysed per minute an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 42 publications
6
46
1
3
Order By: Relevance
“…The level of cell-substratum adhesion by neuronal cells directly correlates with the level of AChE expression [25]. Further, it has been suggested that breast epithelial cells may produce AChE for membrane attachment and hydrophilic BuChE for secretion [34]. Here we have shown the increased adhesion to Fibronectin of colon tumor cells overexpressing AChE.…”
Section: Discussionsupporting
confidence: 55%
“…The level of cell-substratum adhesion by neuronal cells directly correlates with the level of AChE expression [25]. Further, it has been suggested that breast epithelial cells may produce AChE for membrane attachment and hydrophilic BuChE for secretion [34]. Here we have shown the increased adhesion to Fibronectin of colon tumor cells overexpressing AChE.…”
Section: Discussionsupporting
confidence: 55%
“…The percentage of each AChE form was estimated by comparing the AChE activity under each peak area and under the entire profile. The distinct migration of ChE components depending on the detergent (Brij 96 or Triton X-100) added to sucrose gradients showed their amphiphilic properties, which were further confirmed using hydrophobic chromatography in phenyl-agarose [18,19]. The asymmetric structure of 16.2S AChE was assessed by cleaving its ColQ tail with collagenase [20].…”
Section: Methodsmentioning
confidence: 77%
“…If the overexpression of AChE in Caco-2 cells is associated with differentiation, the under-expression may reflect the shifting of gut mucosal cells to a less differentiated state. The down-regulation of AChE and BuChE in colorectal carcinoma, the increase in AChE besides the drop in BuChE activity in breast cancer [18], the fall of AChE but not of BuChE activity in metastasized lymph nodes [20], and the variation of both activities in lung tumors depending on their histological features [15] indicate that the change in ChE activity depends on the kind of cell from which the tumor originates. This view agrees with the variable expression of AChE in proliferating cell systems, so that cell division is associated with up-regulation of AChE in mouse hematopoiesis (after transient blockade of its expression) [36], but with down-regulation in human hematopoiesis [37], megakaryocytopoiesis [38], and osteogenesis [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations